Robotics: Science and Systems XVI 2020
DOI: 10.15607/rss.2020.xvi.002
|View full text |Cite
|
Sign up to set email alerts
|

Swoosh! Rattle! Thump! - Actions that Sound

Abstract: Fig. 1: Using Tilt-Bot, we collect 15,000 interactions on 60 different objects by tilting them in a tray. When sufficiently tilted, the object slides across the tray and hits the walls of the tray. This generates sound, which is captured by four contact microphones mounted on each side of the tray. An overhead camera records visual (RGB+Depth) information, while the robotic arm applies the tilting actions through end-effector rotations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Additionally, Gandhi et al introduce the sound information for a richer environment understanding. The interaction between the sound and robotic action is investigated [13]. In the proposed MQA task, the robot is also required to have a semantic understanding of the environment.…”
Section: Semantic Understanding In Robotic Manipulationmentioning
confidence: 99%
“…Additionally, Gandhi et al introduce the sound information for a richer environment understanding. The interaction between the sound and robotic action is investigated [13]. In the proposed MQA task, the robot is also required to have a semantic understanding of the environment.…”
Section: Semantic Understanding In Robotic Manipulationmentioning
confidence: 99%
“…Recent techniques in visual question answering [49] and language grounding [55,32] allow robots to answer questions about objects and describe objects with natural language. Haptic [45,40] and auditory data [20,25] have also helped robots interpret salient features of objects beyond vision. Interactive perception can further leverage a robot's exploratory actions to reveal sensory signals that are otherwise not observable [9,56,14,61,2,8,59].…”
Section: A Semantic Reasoning In Roboticsmentioning
confidence: 99%
“…To address this problem, several lines of research have shown that incorporating a variety of sensory modalities is the key to further enhance the robotic capabilities in recognizing multisensory object properties (see [4] and [21] for a review). For example, visual and physical interaction data yields more accurate haptic classification for objects [11], and non-visual sensory modalities (e.g., audio, haptics) coupled with exploratory actions (e.g., touch or grasp) have been shown useful for recognizing objects and their properties [5,10,15,24,30], as well as grounding natural language descriptors that people use to refer to objects [3,39]. More recently, researchers have developed end-to-end systems to enable robots to learn to perceive the environment and perform actions at the same time [20,42].…”
Section: Data Augmentationmentioning
confidence: 99%